Analysis of Macroeconomic Factors on JCI Stock Returns for the Period of 2001-2009 - Nirmalasari, Evita (Journal of Business and Management, 2012)
Many people find the perfect investment strategy that can help every investor to invest their money in stock exchange. Since, stock index movement in a country certainly cannot be separated from the conditions of the country's macroeconomic, this research will focus it to the several macroeconomic factors that may affect the return of stock indices such as inflation, SBI rate, money supply, exchange rate, net foreign flow, oil price, and how big the influence of these factors on the movement of stock using the JCI as sample index from period of January 2001–December 2009. Therefore, the main problems to be answered in this research are to find the right model of calculation, partial, and jointly correlation between macroeconomic variables and JCI returns. Since the data that have been examined has a deviation of one of the classical assumption which is heteroscedasticity problems, a sophisticated model, ARCH/GARCH was used to calculate the result.. Keywords : investment, macroeconomics, JSI return, ARCH/GARCH